STRATEGI PENINGKATAN MUTU PENDIDIKAN MELALUI PENERAPAN MANAJEMEN BERBASIS SEKOLAH DI SD NEGERI 02 BANTARBOLANG KABUPATEN PEMALANG - Lilik Septiyani; Soegito Soegito; Nurkolis Nurkolis (Jurnal Manajemen Pendidikan (JMP), 2016)
National Education System in the explanation of Article 51 according to UU No. 20/2003, paragraph 1 is explained that "school-based management is a form of autonomy of management education in the educational unit, in this case the principal or madrassas, and the teacher is assisted by a committee of school in managing educational activities". Decentralization of education makes community participation is essential for the life of the school. Collaboration school autonomy by involving the school community and the community's role will directly give birth to the management of the school with School Based Management.Research shows the implementation of School Based Management in Elementary School 02 Bantarbolang Pemalang have school leadership strong, meaning Chief Sekoleh has a strong role in mobilizing all the educational resources available, able to realize the vision, mission, goals and objectives school through a planned and phased program. Elementary School 02 Bantarbolang Pemalang have a principle of independence, accountability, transparency, and strong partnerships that school that provides easy access to information to the school community and the public on what is being done with school by utilizing various communication channels